2020
DOI: 10.1055/s-0039-3402748
|View full text |Cite
|
Sign up to set email alerts
|

Syphilis Immunoassay Signal Strength Correlates with Active Infection in Pregnant Women

Abstract: Objective This study aimed to evaluate the association of ARCHITECT chemiluminescent immunoassay (CIA) signal strength (signal-to-cutoff [S/CO] ratio), with maternal syphilis stage, rapid plasma reagin (RPR) reactivity, and congenital syphilis. Study Design A prospective observational study of reverse syphilis screening was conducted. Pregnant women were screened with CIA. Reactive CIA was reflexed to RPR; particle agglutination test (Treponema pallidum particle agglutination [TPPA]) was performed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…1 (panel A) shows a flow diagram of the syphilis testing in the retrospective study. Multiple studies have shown an association of the signal-to-cutoff (S/CO) value of syphilis immunoassay tests with subsequent positive confirmatory testing indicating either past or current infection [1] , [2] , [3] , [4] . In the reverse algorithm, confirmation testing typically entails RPR as the next test following a positive syphilis antibodies result [5] .…”
Section: Data Descriptionmentioning
confidence: 99%
“…1 (panel A) shows a flow diagram of the syphilis testing in the retrospective study. Multiple studies have shown an association of the signal-to-cutoff (S/CO) value of syphilis immunoassay tests with subsequent positive confirmatory testing indicating either past or current infection [1] , [2] , [3] , [4] . In the reverse algorithm, confirmation testing typically entails RPR as the next test following a positive syphilis antibodies result [5] .…”
Section: Data Descriptionmentioning
confidence: 99%
“…However, false-negatives can occur with TPPA because of the defects in coating and antigen selection, and the subjective judgment of results [ 5 ]. It has also been reported that a certain percentage of biological false positives can be detected with TPPA [ 5 – 7 ]. In this study, samples with inconsistent results of preliminary screening of anti-TP antibodies by ELISA and retest by TPPA were taken as experiment subjects for other WB tests.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that a certain percentage of biological false positives can be detected with TPPA (5)(6)(7). In this study, samples with inconsistent results of preliminary screening of anti-TP antibodies by ELISA and retest by TPPA were taken as objects.…”
Section: Introductionmentioning
confidence: 99%